Project Daedalus: An Earnest Play of Building Between Storytelling and Metaphors - Matyiku, Anca (Writingplace, 2018)
Every place is built around shared values, norms, histories and myths that are assumed, implied, or tactfully left unsaid. Architecture is at its core an accomplice to the untidy matter of human stories and aspi- rations, even if the architect’s work typically results in concrete and measurable compositions. The making of architecture, in every one of its pleasures and difficulties, involves the crucial task of interpreting among tangible materials and the multitude of implicit forces that characterize a particular place. My proposition is that literature and storytelling can play an essential role in this interpretive task, and that they are especially fruitful for architectural pedagogy. This article reflects on this proposition via examples of student work pro- duced under my guidance at McGill University.The work was the result of an exploratory design project structured around Daedalus, the prototypical figure of the ancient Greek architect best known for his craftsmanship and cunning intelligence. His works – amongst them the legendary labyrinth that enclosed the half-man half-bull Minotaur – were said to inspire a profound sense of wonder mingled with fear, akin to the presence of the divine. Project Daedalus was not a studio project that resulted in a building design but an elective course which, taking its cue from Daedalus, focused on architectural craft. It asked the students to concentrate on ‘building’ as a verb rather than a noun, an action rather than an object. The final projects emerged through a series of exercises that required students to translate between tactile and literary mediums. With Project Daedalus, literary constructs suspended commitment to a final and concrete outcome, while opening up the opportunity for play.